2022
DOI: 10.1292/jvms.21-0470
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of chicken anemia viruses newly isolated from diseased chicks in Japan in 2020

Abstract: In this study, a total of nine chicken samples obtained from two broiler flocks in Oita and Tottori prefectures in 2020 were examined for Chicken anemia virus (CAV) infection. The samples were collected from clinically suspected flocks and diseased chickens. The CAV genome was detected in all nine samples tested by real-time PCR. Phylogenetic analyses and sequence comparisons of the full-length VP1 gene sequences indicated that all the Japanese CAV strains obtained in this study formed a similar cluster of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Furthermore, we confirmed that VP1 interacted with IRF7 by selectively binding to IRF7 with a DBD deletion (aa 143–492) which was reported to be essential for the dimerization and phosphorylation of IRF7 ( Wang et al., 2020 ). In our study, we found for the first time that CAV VP1 is a potent inhibitor of the crash-STING pathway that binds to IRF7 and disrupts IRF7 dimerization, which ultimately can reduce IFN-β production and weaken the innate antiviral response ( Christensen et al., 2016 ; Dong et al., 2022 ) ( Figure 7 ).
Figure 7 Schematic of the inhibitory effect of CAV VP1 on the cGAS-STING pathway.
…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, we confirmed that VP1 interacted with IRF7 by selectively binding to IRF7 with a DBD deletion (aa 143–492) which was reported to be essential for the dimerization and phosphorylation of IRF7 ( Wang et al., 2020 ). In our study, we found for the first time that CAV VP1 is a potent inhibitor of the crash-STING pathway that binds to IRF7 and disrupts IRF7 dimerization, which ultimately can reduce IFN-β production and weaken the innate antiviral response ( Christensen et al., 2016 ; Dong et al., 2022 ) ( Figure 7 ).
Figure 7 Schematic of the inhibitory effect of CAV VP1 on the cGAS-STING pathway.
…”
Section: Discussionmentioning
confidence: 77%
“…Chicken anemia virus ( CAV ), a nonenveloped small ssDNA virus, is a ubiquitous avian pathogen that causes an immunosuppressive infectious anemia disease. This virus represses the immune responses of the host and thus, infected chickens are more susceptible to other pathogens ( Wani et al., 2006 ; Schat, 2009 ; Dong et al., 2022 ). As a result, great economic loss has been caused by CAV in the poultry industry globally.…”
Section: Introductionmentioning
confidence: 99%